Breakdown of the Impeller Wheel of a TG2 Kaplan Turbine - Peter Palcek; Maria Chalupova (Communications - Scientific letters of the University of Zilina, 2006)
The paper deals with the investigation of the breakdown of the impeller wheel of a TG2 Kaplan turbine with the power of 36 MW that was operating for only 6.5 years. To find the cause, both methods of investigation of mechanical properties and analyses of microstructure and micrographics were used. On the basis of the results of individual analyses we found out that the primary cause of the impeller wheel breakdown was inconvenient material of the servomotor rod.